2016
DOI: 10.1371/journal.pone.0146400
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and Acute Pain in Patients Undergoing Orthopedic Surgery

Abstract: ObjectiveThere is a limited information about the role of Substance P (SP) in acute pain nociception following surgical stimulation in patients with a chronic inflammatory state not to mention the link between this neuropeptide level changes and intensity of pain. The goal of the research was to find the correlation between SP level changes and acute pain intensity in patients with rheumatoid arthritis undergoing elective orthopedic surgery.Material and MethodsPatients with rheumatoid arthritis (RA) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…SP levels were found clinically to be elevated following orthopedic surgery, with increasing levels of SP correlating with increasing levels of acute pain intensity (Lisowska et al, 2016). Previously, we found SP to be an endogenous agonist of Mrgprb2 (McNeil et al, 2015), so we tested whether SP injected into the hindpaws of mice was capable of recruiting innate immune cells.…”
Section: Substance P Promotes Innate Immune Cell Recruitment Via Actimentioning
confidence: 99%
“…SP levels were found clinically to be elevated following orthopedic surgery, with increasing levels of SP correlating with increasing levels of acute pain intensity (Lisowska et al, 2016). Previously, we found SP to be an endogenous agonist of Mrgprb2 (McNeil et al, 2015), so we tested whether SP injected into the hindpaws of mice was capable of recruiting innate immune cells.…”
Section: Substance P Promotes Innate Immune Cell Recruitment Via Actimentioning
confidence: 99%
“…A decrease in the serum level of SP has not been reported previously. Previous study has suggested a positive correlation between the systemic SP level and pain nociception (11). Lisowska et al found that among patients with rheumatoid arthritis, the extent of pain after total knee arthroplasty was positively correlated with the serum level of SP (11).…”
Section: Discussionmentioning
confidence: 98%
“…Further research is required focusing on NMT's influence on biological and chemical injury agents, e.g., burns and postoperative conditions. P substance in serum is closely associated with the occurrence of acute pain (Blow, 2018;Lisowska et al, 2016), and further research is required on whether NMT can influence P substance. The development of NMT in the management of acute pain in cancer and postoperative care also requires further research, e.g., in terms of surgical wound care.…”
Section: Discussionmentioning
confidence: 99%